The Psychological, Social, and Health Impacts of Cigarette Smoking on Youth: A Sociological investigation in Sindh, Pakistan - Khoso, Abdul Rasool; Bhutto, Shahnaz; Asif, Muhammad; Suyuhan, Wang (Symbiohealth, 2025)
Cigarette consumption represents a noteworthy health crisis internationally, posing risks especially to the youth. It is listed among the primary avoidable reasons for death internationally, with over 8 million casualties yearly, where more than 7 million are due to the direct use of tobacco and about 1.2 million are caused by second-hand smoke exposure. This research aims to investigate the psychological, social, and health risks to youth, particularly in regions like Sindh, Pakistan. This study investigates these impacts through a cross-sectional mixed-methods design involving 310 youth aged 15–25 years in Larkana, Sindh. Quantitative data was collected via structured questionnaires assessing social, psychological, and health impacts, while qualitative insights were gathered from semi-structured interviews. The quantitative analysis was done using SPSS to gather the actual figures, while the qualitative analysis was done using NVIVO software. The results revealed key predictors of social, psychological, and health impacts of smoking. Regression analysis showed that peer influence (β = 0.25, p < 0.001), smoking duration (β = 0.12, p < 0.001), and age (β = 0.08, p < 0.001) were significant predictors of social impacts. Psychological impacts were significantly influenced by smoking frequency (β = 0.18, p < 0.001), anxiety scores (β = 0.30, p < 0.001), and age (β = -0.04, p = 0.046). Health impacts were primarily driven by smoking duration (β = 0.22, p < 0.001), craving scores (β = 0.35, p < 0.001), and education level (β = -0.10, p = 0.013). Qualitative findings highlighted peer pressure, stress relief, and societal stigma as key drivers of smoking initiation. Health concerns and limited awareness of long-term risks further exacerbated smoking prevalence. The study concludes, peer pressure and social acceptance were key factors driving smoking habits, which were linked to anxiety, depression, and chronic health issues like respiratory problems. The study highlights the need to reduce stigma, raise public health awareness, and improve access to smoking cessation support, particularly for women. Policy recommendations include the need for culturally relevant anti-smoking campaigns, increased access to cessation resources, and the integration of tobacco education into school curricula.